Konstruktivisme Dalam Pendidikan: (Sebuah Kajian Filosofis) - Azhar, Imam (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2016)
In simple terms constructivism assumes that one's knowledge is the construction (formation) of someone who knows something. Resnick (1983), which attributes him to science and mathematics, concludes that 'the learned person forms understanding'. While Bettencourt (1989) says that people who learn not only imitate or reflect what is taught or that he reads, but creates understanding.